Preparation method of quaternary solid waste-based cementing material and solidification method of shield muck

By preparing four-part solid waste-based gelling materials, mixing them with shield slag to form composite gelling materials, the problem of shield slag treatment is solved, the mechanical properties and resource utilization of the materials are improved, and green environmental protection and sustainable development are promoted.

CN119822656AInactive Publication Date: 2025-04-15OCEAN UNIV OF CHINA +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510104476.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The amount of slag generated during shield construction is large and not effectively treated, resulting in changes in soil structure and potential dangers.

Method used

Using the preparation method of quadruple solid waste-based gelling material, by mixing calcium carbide slag, blast furnace slag micro powder, fly ash and graphene oxide in a specific proportion, and calcining and stirring at a certain temperature, a three-dimensional network product is formed to wrap and fill shield slag particles.

Benefits of technology

The mechanical properties of shield slag composite cementitious materials have been improved, the resource utilization of shield slag has been realized, and green environmental protection and sustainable development have been promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822656A_ABST
    Figure CN119822656A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to a preparation method of a quaternary solid waste-based cementing material and a curing method of cement shield muck. The quaternary solid waste-based cementing material is prepared from the carbide slag, the blast furnace slag micropowder, the fly ash and the graphene oxide, and then the shield muck is cured by using the quaternary solid waste-based cementing material. Not only can the utilization of the shield muck be realized, but also the mechanical property of the solidified shield muck can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a method for preparing a quaternary solid waste-based cementitious material and a method for solidifying cement shield slag. Background Art

[0002] With the large-scale construction of tunnel projects in my country, the amount of slag generated during shield construction has continued to rise. According to statistics, the amount of slag from development and construction projects in large and medium-sized cities in China has accounted for 15% to 20% of the total urban garbage discharge, and most of these engineering slag has not been harmlessly treated and effectively utilized as a resource.

[0003] The slag produced by shield tunnels, especially large-diameter slurry shields, not only has a high output and occupies a large area, but also has a high moisture content and strong fluidity. In addition, there are various additives, such as flocculants and high molecular polymers, which make the treatment very complicated. If the shield slag is transported to a mine or landfill for direct landfill, it may cause changes in the soil structure, enter the underground crushed soil, increase the fluidity of the soil, form a swamp effect, and become a long-term potential danger. Therefore, it is urgent to propose an effective treatment method for shield slag. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and propose a solidification method of a quaternary solid waste-based cementitious material and shield slag, which realizes the utilization of shield slag and can improve the mechanical properties of the shield slag after solidification.

[0005] The technical solution of the present invention is: a method for preparing a quaternary solid waste-based gelling material, which comprises the following steps:

[0006] A1. Carbide slag, blast furnace slag powder and fly ash are mixed in a mass ratio of (4-5): (4-5): (1-2), and the mixed materials are calcined at 200-250° C. and stirred to obtain a dry material of a ternary solid waste-based cementitious material;

[0007] A2. Adding graphene oxide dry material to the ternary solid waste-based gelling material dry material, wherein the addition amount of the graphene oxide dry material is 0.6%-1% of the ternary solid waste-based gelling material dry material, to obtain gelling material powder;

[0008] A3, the cementitious material powder is uniformly mixed with water to obtain a slurry, and the mass ratio between the cementitious material powder and water is 1: (0.9-1.1);

[0009] A4. Cast the slurry obtained in step A3, and cure the cast sample to obtain a quaternary solid waste-based cementitious material.

[0010] In the present invention, in step A1, the mass ratio of carbide slag, blast furnace slag powder and fly ash is 4:5:1.

[0011] The main oxidizing component of carbide slag is calcium oxide, which has a content of more than 67%. The particle size of carbide slag is 0.15-3.1μm, and the median particle size is 1.313μm.

[0012] The pH value of carbide slag is 12-13.

[0013] The main components of the blast furnace slag powder include CaO, Al2O3 and SiO2;

[0014] The main components of the fly ash include CaO, Al2O3 and SiO2, wherein the content of CaO is less than 10%;

[0015] The fly ash particles are porous honeycomb-shaped and have a particle size range of 0.5-300μm.

[0016] The present application also proposes a method for solidifying shield slag using the quaternary solid waste-based cementitious material prepared by the above method, which comprises the following steps:

[0017] B1. Dry the shield slag raw materials to make the moisture content of the shield slag raw materials no more than 0.2%;

[0018] B2. Add quaternary solid waste-based cementitious materials to the dried shield slag raw materials, the mass ratio of quaternary solid waste-based cementitious materials to shield slag raw materials is 5%-10%, and the shield slag raw materials and quaternary solid waste-based cementitious materials are evenly mixed to form a mixture of slag and cementitious materials;

[0019] B3. Add water to the mixture of slag and cementitious material, with the mass ratio of the mixture to water being 1:(0.9-1.1), stir evenly and form a slurry;

[0020] B4. Pour the slurry and perform curing. After demoulding, shield slag composite cementitious material is obtained. The shield slag composite cementitious material can be used as roadbed material.

[0021] The mineral composition of shield slag includes quartz and felsic, with SiO2 content not less than 68.19% and Al2O3 content reaching 15.23%;

[0022] Fine particles smaller than 0.075 mm are no less than 70% of the shield slag minerals, the uniformity coefficient is 85, and the curvature coefficient is 0.42.

[0023] The mass ratio of quaternary solid waste-based cementitious materials to shield slag raw materials is 10%.

[0024] The beneficial effects of the present invention are:

[0025] The cementitious products inside the quaternary solid waste-based cementitious materials continue to grow and develop, gradually forming a three-dimensional network product, the product is CSH. The shield slag particles are wrapped by the three-dimensional network structure CSH, filling the cracks between the particles. Graphene oxide is used to improve the problem of weak initial strength of ultrafine slag powder, so that the structure of the shield slag composite cementitious material formed after solidification tends to be stable, and the strength is further improved, thereby improving the mechanical properties of the shield slag composite cementitious material, realizing the resource utilization of shield slag, and helping to promote green environmental protection and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is an electron microscope image of a solidified sample obtained by cement solidification of shield slag;

[0027] Figure 2 This is an electron microscope image of a solidified sample obtained by solidifying shield slag with the quaternary solid waste-based cementitious material described in this application;

[0028] Figure 3 The external appearance characteristics of the sample samples prepared by the methods described in Example 1 to Comparative Example 3 are compared;

[0029] Figure 4 It is the relationship between the age of shield slag solidified composite cementitious material and the unconfined compressive strength;

[0030] Figure 5 It is a relationship diagram between the mass ratio of quaternary solid waste-based cementitious materials and shield slag and the unconfined compressive strength. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0032] In the following description, specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways than those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0033] The present application proposes a method for preparing a quaternary solid waste-based cementitious material, which comprises the following steps.

[0034] In the first step, carbide slag, blast furnace slag powder and fly ash are mixed in a mass ratio of (4-5): (4-5): (1-2). The mixed materials are calcined at 200-250° C. and stirred evenly to obtain a dry material of a ternary solid waste-based cementitious material.

[0035] In this embodiment, the carbide slag used is taken from an industrial gas company in Qingdao, Shandong Province, and is an industrial waste residue produced after carbide is hydrolyzed to obtain acetylene gas. The carbide slag contains a large amount of Ca(OH)2, is an industrial waste residue with good alkalinity, has a water content of 29.8%, and is in a gray powder at room temperature. The pH value of the carbide slag is about 12.5. Calcium oxide is the main oxide component of the industrial waste residue, and its content exceeds 67%. The particle size distribution of the carbide slag is 0.15-3.1μm, and the median particle size is 1.313μm.

[0036] Blast furnace slag is taken from the granulated blast furnace slag after water quenching in a steel plant in Jinan, Shandong. It is a highly reactive volcanic ash material with the main components of CaO-Al2O3-SiO2 and is a white powder at room temperature. Blast furnace slag is a metallurgical solid waste residue produced in the process of smelting pig iron. Its activity is closely related to the cooling process. The blast furnace slag obtained by rapid cooling such as water quenching will contain a certain amount of glassy substances and has potential hydraulic gelling properties.

[0037] Fly ash is taken from the Class I fly ash of a power plant in Shandong. It is collected from the flue gas discharged from the coal-fired power plant. It is a low-reactivity volcanic ash material and the main solid waste discharged from the coal-fired power plant. The main components are CaO, Al2O3 and SiO2, of which the CaO content is less than 10%. It belongs to Class F fly ash and is gray powder at room temperature. The fly ash particles are porous honeycomb structure, with a large specific surface area and high adsorption activity. The particle size range is 0.5-300μm.

[0038] In the second step, graphene oxide dry material is added to the ternary solid waste based cementitious material dry material, and the addition amount of graphene oxide dry material is 0.6%-1% of the ternary solid waste based cementitious material dry material to obtain cementitious material powder.

[0039] The third step is to mix the cementitious material powder and water evenly to obtain a slurry. The mass ratio between the cementitious material powder and water is 1: (0.9-1.1).

[0040] The fourth step is to fill the slurry after adding water into the test mold in three layers, compact each layer, and roughen the surface slurry after each round of compaction.

[0041] The sample was placed in a standard curing box with a relative humidity of 95% and a temperature of 20°C for 24 hours. After curing, the sample was demoulded to obtain a quaternary solid waste-based cementitious material for curing shield slag.

[0042] The present application also proposes a method for solidifying shield slag using the quaternary solid waste-based cementitious material prepared by the above method, and the method includes the following steps.

[0043] The first step is to place the shield slag raw materials in a drying environment at 105°C for 24 hours to make the moisture content of the shield slag raw materials no more than 0.2%.

[0044] In this embodiment, the slag soil used is from a large-diameter shield tunnel project in Qingdao. The mineral composition of the shield slag soil is mainly quartz and feldspar, with a SiO2 content of 68.19%, an Al2O3 content of 15.23%, a stone chip content of 26.2%, a fine stone powder content of 54.9%, and an ultrafine stone powder content of 18.9%. The fine particles smaller than 0.075 mm account for more than 70% of the total weight, which is fine-grained soil, with an uneven coefficient of 85 and a curvature coefficient of 0.42, indicating poor gradation.

[0045] The second step is to add the prepared quaternary solid waste-based cementitious material into the dried shield slag raw material, wherein the mass ratio of the quaternary solid waste-based cementitious material to the shield slag raw material is 5%-10%.

[0046] The shield slag raw materials and the quaternary solid waste-based cementitious materials are mixed evenly to form a mixture of slag and cementitious materials.

[0047] The third step is to add water to the mixture formed in the second step, and the mass ratio of the mixture to water is 1: (0.9-1.1). According to the above mass ratio, weigh the required amount of water, add the water to the mixture of slag and cementitious material, and stir evenly for 5 minutes to form a slurry.

[0048] The fourth step is to use a cylindrical test mold with an inner diameter of 50mm and a height of 100mm, with a molding compaction degree of 98%. The slurry obtained after adding water is injected into the test mold in three layers. Each layer is tamped, and the surface slurry is roughened after each round of tamping.

[0049] The maximum particle size of the slag is 4.75 mm. The ratio of the minimum size (diameter) of the prepared sample, 50 mm, to the maximum particle size of 4.75 mm is 10.53, so the particle size effect of the material can be ignored.

[0050] The samples were subjected to standard curing in a standard curing room at a temperature of 20±2°C and a relative humidity of more than 95%. After curing for 24 hours, the samples were demoulded to obtain shield slag composite cementitious material, which can be used as roadbed material.

[0051] In the preparation process of quaternary solid waste-based cementitious materials, calcium carbide slag is hydrolyzed to obtain Ca 2+ and OH - The active glass minerals such as Si-O-Si bonds and Si-O-Al bonds in blast furnace slag and fly ash will be OH - Erosion, generating [SiO4] 4- and [AlO4] 5-, and finally, through a series of polycondensation-recombination reactions, alkali-activated products such as CSH, CAH, and CASH with gelling properties are generated. These alkali-activated products are mainly flocculent and distributed on the surface of the slag particles. The generated alkali-activated products are cemented and filled with slag particles of different sizes, and fill each other, thereby reducing the cracks inside the sample, and the gelling products overlap less with each other. With the increase of curing age, these internal gelling products will continue to grow and develop, and the overlap between the products is obvious, gradually forming a three-dimensional network product, the product is CSH, and the slag particles are almost covered by the three-dimensional network structure CSH, and the connection between the particles is tighter, which reduces the specific surface area inside the sample. The three-dimensional network structure CSH gel is a micro-droplet-shaped cluster formed by the accumulation of long mallet-shaped particles arranged in a regular and close manner. The micro-cluster units further aggregate with other units during the hydration process to form larger clusters, and finally form a three-dimensional network structure CSH gel structure. The slag particles are wrapped by the three-dimensional network structure CSH, filling the cracks between the particles, and the overall structure tends to be stable. At the same time, graphene oxide (GO) is used to improve the problem of weak initial strength of ultrafine slag powder, the strength is further improved, the mechanical properties of the overall material are enhanced, and excellent solid waste-based cementitious materials are prepared at a lower cost.

[0052] like Figure 1 The electron microscope image of the solidified sample obtained by cement solidification of shield slag is shown. Figure 2 This is an electron microscope image of a solidified sample obtained by solidifying shield slag with the quaternary solid waste-based cementitious material described in this application. Figure 1 and Figure 2 It can be seen that the quaternary solid waste-based cementitious material proposed in this application has a better gap filling effect, thereby enhancing the mechanical properties of the cured sample.

[0053] Example 1

[0054] In this embodiment, carbide slag, blast furnace slag powder and fly ash are mixed in a mass ratio of 4:5:1 to prepare a ternary solid waste-based gel material dry material, and graphene oxide dry material is added, and the dosage of graphene oxide dry material is 1% of the ternary solid waste-based gelling material dry material to prepare a quaternary solid waste-based gelling material.

[0055] The mass ratio between the quaternary solid waste-based cementitious material and the shield slag is 10%.

[0056] After the quaternary solid waste-based cementitious material is mixed with the shield slag, a mixture of slag and cementitious material is obtained. The required amount of water is weighed according to a mass ratio of 1:1 between the mixture and water, and the water is added to the mixture and stirred evenly to obtain a slurry, and after pouring, the shield slag solidified composite cementitious material is obtained.

[0057] The shield slag solidified composite cementitious material obtained in this embodiment was cured for 7 days and 28 days respectively under standard curing conditions of temperature of 20° C. and humidity of 95%, and the unconfined compressive strength of the material samples in this embodiment was tested.

[0058] Example 2

[0059] In this embodiment, carbide slag, blast furnace slag powder and fly ash are mixed in a mass ratio of 4:4:2, and 1% graphene oxide is added to prepare a quaternary solid waste-based cementitious material.

[0060] The rest is the same as in Example 1.

[0061] The shield slag solidified composite cementitious material obtained in this embodiment was cured for 7 days and 28 days respectively under standard curing conditions of temperature of 20° C. and humidity of 95%, and the unconfined compressive strength of the material samples in this embodiment was tested.

[0062] Example 3

[0063] In this embodiment, carbide slag, blast furnace slag powder and fly ash are mixed in a mass ratio of 5:4:1, and 1% graphene oxide is added to prepare a quaternary solid waste-based cementitious material.

[0064] The rest is the same as in Example 1.

[0065] The shield slag solidified composite cementitious material obtained in this embodiment was cured for 7 days and 28 days respectively under standard curing conditions of temperature of 20° C. and humidity of 95%, and the unconfined compressive strength of the material samples in this embodiment was tested.

[0066] Comparative Example 1

[0067] In this comparative example, PO42.5 cement was used instead of the quaternary solid waste-based gel material in Example 1 to solidify the shield slag.

[0068] The rest is the same as in Example 1.

[0069] The shield slag solidified composite cementitious material obtained in this embodiment was cured for 7 days and 28 days respectively under standard curing conditions of temperature of 20° C. and humidity of 95%, and the unconfined compressive strength of the material samples in this embodiment was tested.

[0070] Comparative Example 2

[0071] In this comparative example, the mass ratio between the quaternary solid waste-based cementitious material and the shield slag is 6%.

[0072] The rest is the same as in Example 1.

[0073] The shield slag solidified composite cementitious material obtained in this embodiment was cured for 7 days and 28 days respectively under standard curing conditions of temperature of 20° C. and humidity of 95%, and the unconfined compressive strength of the material samples in this embodiment was tested.

[0074] Comparative Example 3

[0075] In this comparative example, the mass ratio between the quaternary solid waste-based cementitious material and the shield slag is 8%.

[0076] The rest is the same as in Example 1.

[0077] The shield slag solidified composite cementitious material obtained in this embodiment was cured for 7 days and 28 days respectively under standard curing conditions of temperature of 20° C. and humidity of 95%, and the unconfined compressive strength of the material samples in this embodiment was tested.

[0078] The test blocks obtained in Example 1 to Comparative Example 3 were tested respectively to test the compressive strength of the test blocks obtained by the above different method steps. The test results are shown in Table 1.

[0079] Table 1 Compressive strength of test blocks at different ages

[0080] sample 7d compressive strength, MPa 28d compressive strength, MPa Example 1 1.86 3.15 Example 2 1.84 3.07 Example 3 1.79 3.02 Comparative Example 1 1.21 2.58 Comparative Example 2 1.51 2.87 Comparative Example 3 1.65 2.92

[0081] From Table 1 and Figure 4 It can be seen that when the quaternary solid waste-based cementitious material prepared in this application is used to solidify shield slag, the mechanical strength of the solidified shield slag composite cementitious material can be greatly improved. The greater the mass ratio of the quaternary solid waste-based cementitious material to the shield slag, the stronger its lifting capacity.

[0082] From Table 1 and Figure 5 It can be seen that when the mass ratio of the quaternary solid waste-based cementitious material to the shield slag exceeds a certain threshold, its enhancement effect on the mechanical properties gradually becomes regionally flat, which shows that there is an optimal mass ratio between the quaternary solid waste-based cementitious material and the shield slag. After exceeding this ratio, the further increase of the quaternary solid waste-based cementitious material has little effect on improving the mechanical strength of the shield slag composite cementitious material. In this application, the optimal mass ratio between the quaternary solid waste-based cementitious material and the shield slag is 10%.

[0083] In addition, under the conditions of the same age and the same mass ratio of quaternary solid waste-based cementitious materials, when the mass ratio of carbide slag, blast furnace slag powder and fly ash is 4:5:1, the compressive strength of the prepared shield slag composite cementitious material is higher.

[0084] The above is a detailed introduction to the preparation method of the quaternary solid waste-based cementitious material and the solidification method of shield slag provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method and core ideas of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The above description of the disclosed embodiments enables professional and technical personnel in this field to implement or use the present invention. Various modifications to these embodiments will be obvious to professional and technical personnel in this field, and the general principles defined in this article can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown in this article, but will conform to the widest range consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a quaternary solid waste-based cementitious material, characterized in that: The following steps are involved: A1. Carbide slag, blast furnace slag powder and fly ash are mixed in a mass ratio of (4-5): (4-5): (1-2), and the mixed materials are calcined at 200-250° C. and stirred to obtain a dry material of a ternary solid waste-based cementitious material; A2. Adding graphene oxide dry material to the ternary solid waste-based gelling material dry material, wherein the addition amount of the graphene oxide dry material is 0.6%-1% of the ternary solid waste-based gelling material dry material, to obtain gelling material powder; A3, the cementitious material powder is uniformly mixed with water to obtain a slurry, and the mass ratio between the cementitious material powder and water is 1: (0.9-1.1); A4. Cast the slurry obtained in step A3, and cure the cast sample to obtain a quaternary solid waste-based cementitious material.

2. The method for preparing quaternary solid waste-based cementitious materials according to claim 1, characterized in that: In step A1, the mass ratio of carbide slag, blast furnace slag powder and fly ash is 4:5:

1.

3. The method for preparing quaternary solid waste-based cementitious materials according to claim 1, characterized in that: The addition amount of graphene oxide dry material is 1% of the dry material of ternary solid waste-based cementitious material.

4. The method for preparing quaternary solid waste-based cementitious materials according to claim 1, characterized in that: The main oxidizing component of carbide slag is calcium oxide, which has a content of more than 67%. The particle size of carbide slag is 0.15-3.1μm, and the median particle size is 1.313μm. The pH value of carbide slag is 12-13.

5. The method for preparing quaternary solid waste-based cementitious materials according to claim 1, characterized in that: The main components of the blast furnace slag powder include CaO, Al2O3 and SiO2.

6. The method for preparing quaternary solid waste-based cementitious materials according to claim 1, characterized in that: The main components of the fly ash include CaO, Al2O3 and SiO2, wherein the content of CaO is less than 10%; The fly ash particles are porous honeycomb-shaped and have a particle size range of 0.5-300μm.

7. A method for solidifying shield slag using the quaternary solid waste-based cementitious material prepared by the method according to any one of claims 1 to 6, characterized in that: The following steps are involved: B1. Dry the shield slag raw materials to make the moisture content of the shield slag raw materials no more than 0.2%; B2. Add quaternary solid waste-based cementitious materials to the dried shield slag raw materials, the mass ratio of quaternary solid waste-based cementitious materials to shield slag raw materials is 5%-10%, and the shield slag raw materials and quaternary solid waste-based cementitious materials are evenly mixed to form a mixture of slag and cementitious materials; B3. Add water to the mixture of slag and cementitious material, with the mass ratio of the mixture to water being 1:(0.9-1.1), stir evenly and form a slurry; B4. Pour the slurry and perform curing. After demoulding, shield slag composite cementitious material is obtained. The shield slag composite cementitious material can be used as roadbed material.

8. The method for solidifying shield tunneling slag according to claim 7, characterized in that: The mineral composition of shield slag includes quartz and felsic, with SiO2 content not less than 68.19% and Al2O3 content reaching 15.23%; Fine particles smaller than 0.075 mm are no less than 70% of the shield slag minerals, the uniformity coefficient is 85, and the curvature coefficient is 0.

42.

9. The method for solidifying shield slag according to claim 7, characterized in that: The mass ratio of quaternary solid waste-based cementitious materials to shield slag raw materials is 10%.

Citation Information

Cited By

  • All-solid-waste self-excitation muck slurry and preparation method thereof

    CN122277172A